A Bubble Detection Algorithm Based on Sparse and Redundant Image Processing - Ye Tian; Change Zheng; Qiuhong Ke (Institute of Advanced Engineering and Science, 2013)
Deinked pulp flotation column has been applied in wastepaper recycling. Bubble size in deinked pulp flotation column is very important during the flotation process. In this paper, bubble images of deinked pulp flotation column were first caught by digital camera, and then the bubbles were detected by using a detection algorithm based on sparse and redundant image processing. The results show the algorithms are very practical and effective on bubble detection in deinked pulp flotation column. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2604